ANALISIS DETERMINASI PENGHAMBAT PELAPORAN AKUNTANSI SUMBER DAYA MANUSIA - Hamzah, Amir (Jurnal Riset Keuangan dan Akuntansi, 2018)
This study aims to analyze the determination of inhibiting reporting of human resource accounting at Shariah microfinance institutions in Kuningan Regency, with the sample number of 70 respondents of shariah microfinance institutions.          This study used a qualitative descriptive research method and verification with interview or questionnaire technique. Research data were tested using instrument test, classical assumption test, multiple regression test.          The results showed partially variable cost of human resources have a significant positive effect on human resources accounting report, variable measurement of human resources value has a significant positive effect on the human resources accounting report and together show that the variable cost of human resources and measurement value human resources to the accounting reports of human resources. Keywords: Human Resource Cost, Human Resource Measurement Value, Human Resource Accounting Report